Verificado Mexico 2018. Disinformation and fact-checking on elec-toral campaign - Magallón Rosa, Raúl (2019)
The aim of this research is to analyze the use of Twitter by Verificado México during the Mexican electoral campaign of 2018. The project, known as VerificadoMX 2018, brought together a team of more than 90 media outlets and organizations that partnered to verify information about an electoral process that began on March 29 and ended on June 27, 2018. Based on the analysis of the 3116 tweets published from VerificadoMx's Twitter account, a typology of rumors and verifications is proposed for the study of electoral campaigns. From the study of the VerificadoMX Twitter account we must point out that we must distinguish two specific moments that accelerate the verification of facts and speeches: the electoral debates and the electoral day. On the other hand, we can differentiate between rumors of electoral pre-campaign, campaign and post-campaign.